100% Efficient three‐dimensional coronary MR angiography with two‐dimensional beat‐to‐beat translational and bin‐to‐bin affine motion correction. Issue 3 (18th September 2014) - Aitken, Andrew P.; Henningsson, Markus; Botnar, Rene M.; Schaeffter, Tobias; Prieto, Claudia
<x xml:space="preserve">Abstract</x> Purpose To develop a flexible image navigator for 3D coronary MR angiography that allows respiratory motion of variable complexity to be compensated for on different temporal scales. Methods A two‐dimensional (2D) golden radial image navigator is proposed; translational motion is compensated for on a beat‐to‐beat basis, and residual affine motion is compensated for on a bin‐to‐bin basis in a two‐step procedure. The method does not use a respiratory gating window and therefore achieves 100% scan efficiency and a predictable scan time. The proposed method was tested in 11 healthy volunteers and compared against a navigator‐gated and tracked acquisition. Results The proposed method achieved comparable quantitative and qualitative image quality to a 6‐mm navigator‐gated and tracked scan while reducing the scan time by a factor of approximately 2. Combined motion correction using image navigators improved visualization of the coronary arteries in four of 11 subjects in comparison with translational correction only, and image quality was maintained in the remaining cases. In one case, visualization of the left anterior descending coronary artery was degraded using combined correction compared with translation correction only. Conclusions The feasibility of correcting for 2D translational motion on a beat‐to‐beat basis as well as affine motion on a bin‐to‐bin basis has been demonstrated. Magn Reson Med 74:756–764, 2015. © 2014 The Authors. Magnetic Resonance in Medicine Published by Wiley Periodicals, Inc. on behalf of International Society of Medicine in Resonance.